The Effect of the Use of Small Group Discussion Type Active Learning Strategy on Students' Critical Thinking Skills in the Subject of Moral Beliefs at MA Darul Ulum Palangka Raya - Mayasari, Latifah; Supriadi, Gito; Anshari, Muhammad Redha (Dinasti International Journal of Education Management and Social Science, 2025)
Learning of Moral Faith is still dominated by a one-way learning strategy that causes students to be passive and poorly trained in critical thinking, especially in the material of the Kalam science streams. This condition encourages the need for the use of more active learning strategies. This study aims to determine the influence of the Small Group Discussion type Active Learning strategy on students' critical thinking skills. This study uses a pre-experimental quantitative approach with a one-group pretest-posttest design. The population in this study was all students in grade XI of MA Darul Ulum Palangka Raya, while the research sample consisted of 26 students of class XI A. The results showed that there was an effect of the use of Active Learning type Small Group Discussion on students' critical thinking skills in the subject of Moral Faith at MA Darul Ulum Palangka Raya, with a significance value of 0.000 (< 0.05).